State-of-the-Art Technologies and Equipment for Obtaining High-Quality Drinking Water - Goncharuk, V.V.; Baydachny, A.N.; Kucheruk, D.D.; Balakina, M.N. (Science and Innovation, 2024)
A principally new concept of supply quality drinking water to the Ukrainian population have been proposed. It is based on a system of autonomous complexes for water purification directly at the area of consumption. Water treatment autonomous complexes for collective and individual use with biological testing and analytical quality control of drinking water have been developed. The methods for cleaning the tap and other water up to the genetically safe quality are based on a modular concept that provides the possibility of varying the number of modules depending on the composition of source water. The proposed technology and equipment have no analogues in the world by self-cost and complex of problems that have been addressed. Over thousand Vega modular installations and Promin disinfecting vehicles have been implemented in many populated localities throughout Ukraine.